Diagnostic efficacy of mean nocturnal basal impedance, a new parameter for the study of gastroesophageal reflux disease (2018)
Introduction and Objectives: Analysis of nocturnal basal impedance (IBNM) has been proposed as a way to increase accuracy of GERD diagnosis. Our objective was to evaluate the diagnostic performance of this test in a group of patients known to have GERD. Materials and methods: We included 123 individuals: 58 with GERD and 65 healthy controls. They underwent consecutive pH-impedance monitoring between January 2015 and June 2017. All had undergone endoscopy in the 6 months prior to testing. Criteria used for diagnosis of GERD were abnormal acid exposure time (AET > 4.2%), pyrosis and/or regurgitation in the previous 6 months. We found 58 patients with GERD of whom 24 had erosive reflux disease (ERE) and 34 had non-erosive reflux disease (NERD). The remaining 65 were asymptomatic healthy controls with normal endoscopic results and pH impedance monitoring. A second observer who did not know the previous data measurements analyzed all pH impedance monitoring traces for IBMN. Statistical analysis included multiple Bonferroni tests for comparison between groups, linear regression for continuous variables, and receiver operating characteristic (ROC) curve analysis to find high performance IBNM values. The IBNM cutoff point was used for diagnostic precision parameters. Statistical significance was set at p less than 0.01, and 95% confidence intervals were used for all calculations. Results: IBNM measures were significantly lower for patients with ERE and NERD than for the control group (p less than 0.01). A negative correlation was observed between IBNM and acid exposure time values (r = 0.59, p = less than 0.001) and also between IBNM and number of reflux events (r = 0.37, p = less than 0.001). ROC curve analysis found that the area under the curve for IBNM was 0.941 (95% CI: 0.894-0.987), and the cutoff point with the highest efficiency was 1,102 ohms (sensitivity 98.5%, specificity 84.5%). Using this value ( less than 1.102), the IBNM had a sensitivity for detecting GERD of 91% (NERD 86% and ERE 100%) and a specificity of 98%. Conclusion: IBNM has high sensitivity and specificity for diagnosis of GERD. Addition of this test to conventional pH-impedance analysis and current methods for studying GERD can significantly improve our ability to diagnose this disease. © 2018 Asociaciones Colombianas de Gastroenterología, Endoscopia digestiva, Coloproctología y Hepatología.